Cliometrics of Higher Education: Experimental Analysis of the Theory of Glutting - Diebolt, Claude; Jaoul-Grammare, Magali (DEMO, 2016)
The aim of this paper is to study the students' strategy of school choices and to test with an experimental analysis the theory of glutting (Diebolt 2001). It extends an ex- perience carried out in a previous paper (Jaoul-Grammare 2007) and develops an analysis of choices according to individual characteristics. If the experience seems to confirm the theoretical model, revealing a sensitivity to earnings and to the number of available places, with limited rationality in the choice, the study allows to refine these results underlining a significant reverse impact of the gender issue when the choice takes into account the earning or the risk variables.(original abstract)